Facile synthesis of bio-based tetra-functional epoxy resin and its potential application as high-performance composite resin matrix. (1st June 2021) - Qi, Yu; Weng, Zhihuan; Kou, Yan; Li, Jiahui; Cao, Qi; Wang, Jinyan; Zhang, Shouhai; Jian, Xigao
Abstract: In order to meet the increasing performance demands for resin matrix in aerospace industry and fulfill the sustainable development strategy, designment of bio-based epoxy resins with satisfactory comprehensive properties outperforming N, N, N′, N′-tetraglycidyl-4, 4′-diaminodipehnylmethane (TGDDM) for high-end application is of paramount important but also a formidable challenge. Herein, a simple and high-efficient method was proposed to synthesize a bio-based tetra-functional epoxy resin (MTEP) from a sustainable biomass feedstock, magnolol. With 4, 4′-diaminodiphenyl sulfone (DDS) as curing agent, the cured MTEP/DDS showed a record glass transition temperature of 326 °C and an ultrahigh char yield of 52.1%, which was 83 °C and 1.1 times higher than those of TGDDM/DDS, respectively. In addition, the cured MTEP/DDS also exhibited a high flexural modulus of 3991 MPa and storage modulus (at 25 °C) of 3705 MPa, which were all superior to those of TGDDM/DDS. More impressively, thanks to the unique structure of magnolol, the cured MTEP/DDS illustrated lower water absorption in comparison with TGDDM/DDS, and possessed outstanding intrinsic flame retardancy, attaining V-0 rating in UL-94 test. This work adds new members to the synthetic toolbox of high-performance bio-based polymers as composite resin matrix for potential aerospace applications. Highlights: A magnolol-based tetrafunctional epoxy with far-apart epoxy groups was synthesized. It showed a recorded T g of 326 °C and an ultra-high char yield of 52.1%. It exhibited satisfactory intrinsic flame retardancy, passing the UL-94 V0 rating. It exhibited higher comprehensive properties than TGDDM.